La poética de las ideas en el Ecuador Lecturas universales de hombres particulares - Cevallos Rueda, Galo (2014)
The poetic ideas in Ecuador. Universal readings individual men it is a philosophical essay of cultural interpretation, which seeks to highlight the philosophical and artistic splendors of Ecuador from a symbolic hermeneutics. Highlighting the contributions in understanding the universality of Ecuadorian and Latin American man keeping a humanism that reinterprets the cultural past portraying characters of thought and art that left an impression of universality and comprehensive versatility that catapult as poetic hermeneutics of the Latin America culture, questioning and rethinking the universal pseudo - history of Eurocentric bias. The thinker Benjamín Carrión, the poet Jorge Carrera Andrade and the colonial Caspicara sculptor. Great exponents of the original and transcendent spiritual mindset. The show us what to do in their deep sources of an actively constructive culture and aesthetics source.